Changes in synaptic markers after administration of ketamine or psychedelics: a systematic scoping review - Zhornitsky, Simon; Oliva, Henrique N. P.; Jayne, Laura A.; Allsop, Aza S. A.; Kaye, Alfred P.; Potenza, Marc N.; Angarita, Gustavo A. (Frontiers in Psychiatry, 2023)
Background Ketamine and psychedelics have abuse liability. They can also induce “transformative experiences” where individuals experience enhanced states of awareness. This enhanced awareness can lead to changes in preexisting behavioral patterns which could be beneficial in the treatment of substance use disorders (SUDs). Preclinical and clinical studies suggest that ketamine and psychedelics may alter markers associated with synaptic density, and that these changes may underlie effects such as sensitization, conditioned place preference, drug self-administration, and verbal memory performance. In this scoping review, we examined studies that measured synaptic markers in animals and humans after exposure to ketamine and/or psychedelics. Methods A systematic search was conducted following PRISMA guidelines, through PubMed, EBSCO, Scopus, and Web of Science, based on a published protocol (Open Science Framework, DOI: 10.17605/OSF.IO/43FQ9). Both in vivo and in vitro studies were included. Studies on the following synaptic markers were included: dendritic structural changes, PSD-95, synapsin-1, synaptophysin-1, synaptotagmin-1, and SV2A. Results Eighty-four studies were included in the final analyses. Seventy-one studies examined synaptic markers following ketamine treatment, nine examined psychedelics, and four examined both. Psychedelics included psilocybin/psilocin, lysergic acid diethylamide, N,N-dimethyltryptamine, 2,5-dimethoxy-4-iodoamphetamine, and ibogaine/noribogaine. Mixed findings regarding synaptic changes in the hippocampus and prefrontal cortex (PFC) have been reported when ketamine was administered in a single dose under basal conditions. Similar mixed findings were seen under basal conditions in studies that used repeated administration of ketamine. However, studies that examined animals during stressful conditions found that a single dose of ketamine counteracted stress-related reductions in synaptic markers in the hippocampus and PFC. Repeated administration of ketamine also counteracted stress effects in the hippocampus. Psychedelics generally increased synaptic markers, but results were more consistently positive for certain agents. Conclusion Ketamine and psychedelics can increase synaptic markers under certain conditions. Heterogeneous findings may relate to methodological differences, agents administered (or different formulations of the same agent), sex, and type of markers. Future studies could address seemingly mixed results by using meta-analytical approaches or study designs that more fully consider individual differences.